2021
DOI: 10.1002/hyp.14440
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of water resources under a changing climate and human activity in the lower Great Lakes region

Abstract: Globally, the number of people experiencing water stress is expected to increase by millions by the end of the century. The Great Lakes region, representing 20% of the world's surface freshwater, is not immune to stresses on water supply due to uncertainties on the impacts of climate and land use change. It is imperative for researchers and policy makers to assess the changing state of water resources, even if the region is water rich. This research developed the integrated surface water-groundwater GSFLOW mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Many studies had shown that climate change, vegetation types, soil properties and human activities can all affect changes in soil moisture (Yan et al, 2021; Yan et al, 2022; Zhu & Lin, 2011). From a large‐scale and long‐term perspective, climate change and vegetation restoration were the two most important factors leading to changes in soil moisture (Soonthornrangan & Lowry, 2021; Yang et al, 2022). However, through long‐term positioning observations, this study found that changes in soil moisture in SF and SH in karst areas are very significantly correlated with rainfall, and the correlation between changes in soil moisture in 10–20 cm is higher than that in 0–10 cm (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies had shown that climate change, vegetation types, soil properties and human activities can all affect changes in soil moisture (Yan et al, 2021; Yan et al, 2022; Zhu & Lin, 2011). From a large‐scale and long‐term perspective, climate change and vegetation restoration were the two most important factors leading to changes in soil moisture (Soonthornrangan & Lowry, 2021; Yang et al, 2022). However, through long‐term positioning observations, this study found that changes in soil moisture in SF and SH in karst areas are very significantly correlated with rainfall, and the correlation between changes in soil moisture in 10–20 cm is higher than that in 0–10 cm (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…What's more, vegetation can affect soil moisture and response to precipitation through many complex and interactive hydrological processes (Canton et al, 2016; Chen et al, 2007; Rivera et al, 2014). However, from a long‐term perspective, climate factors and vegetation restoration are two important factors leading to changes in soil moisture (Soonthornrangan & Lowry, 2021; Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How quickly and to what extent climate will be altered for cities and their surrounding areas remains of critical importance for decision makers. This is especially true for Great Lakes Region, where much of the Rust Belt cities are located, due to its role in harboring a major fraction of the world's freshwater resources (Soonthornrangsan and Lowry, 2021). Climate change projections with enough detail at the local and regional scales are needed to identify vulnerabilities in these areas so that appropriate adaptation and mitigation strategies can be implemented (Byun and Hamlet, 2018;Byun et al, 2019).…”
Section: Implications For Climate Modelingmentioning
confidence: 99%
“…Nevertheless, an integrated approach is advocated for arid environments such as Wadi Hanifah, where the scarcity of water intensifies pollution effects [ 8 , 23 ] . Recent studies underscore the growing pressures on water resources in such areas due to climate change and anthropogenic activities [ 24 , 25 ] , underscoring the urgency for thorough water quality assessments.…”
Section: Introductionmentioning
confidence: 99%